PEMILIHAN PEGAWAI COLLECTION TERBAIK DENGAN MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) (Study Kasus PT. Bank Mandiri (Persero). Tbk Cab. Kebon Sirih Jakarta) - Imam Budiawan; Ispandi Ispandi; Susan Rachmawati; Wati Erawati; Firstianty Wahyuhening Fibriani (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
In evaluate the performance of employee often caused some fault in deciding of decision, because of lack the time and lake of skills. So, it is needed Decision Support System (DSS) to evaluate performance the best of employee, in this case used methode is Analytical Hierarchy Process (AHP). With this methode expected results can determine the best collection quickly, right and accurate